Morphological and nutritional properties of some Lathyrus species - Basaran U.; Onal Asci O.; Mut H.; Ayan I.; Acar Z. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In this study morphological and chemical properties of Lathyrus species (Lathyrus hirsutus L., L. ochrus L. (DC), L. aphaca L. var affinis, L. laxiflorus ssp. laxiflorus, L. annuus L., L. sphaericus Retz.) grown naturally were investigated in 2003 and 2004 .Some plant properties varied as follows: plant height between 32.50 and 131.00 cm, dry yield/plant between 0.32 and 22.16 g/plant, crude protein of hay between 15.00 and 21.00%.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)